EVALUASI PENGUATAN PENDIDIKAN KARAKTER DALAM PROGRAM SEKOLAH RAMAH ANAK PADA PESERTA DIDIK KELAS IV SD ISLAM RAMAH ANAK DEPOK - Tia Wulandari; Nurrohmatul Amaliyah; Ahmad Kosasih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to evaluate the strengthening of character education implementation within the Child-Friendly School program for fourth-grade students at SD Islam Ramah Anak Depok in terms of context, input, process, and product. This research employs an evaluative approach using the CIPP (Context, Input, Process, Product) model. Data collection techniques include interviews, observations, and documentation studies, while data analysis is conducted through data collection, data reduction, data display, and conclusion drawing. The results indicate that in the context aspect, character education planning is embedded in the school’s vision, mission, and objectives and integrated into the curriculum, which is implemented through learning activities, habituation, and both programmed and non-programmed self-development activities. In the input aspect, the school has prepared qualified educators by providing regular training every three months conducted by supervisors, supported by monitoring and coordination from the principal. In the process aspect, the implementation of character education has generally aligned with the planned program, although some challenges remain, such as students’ low awareness of discipline and independence. In the product aspect, the evaluation results show that the character education program has a positive impact on students’ character development. Overall, the implementation of character education within the Child-Friendly School program at SD Islam Ramah Anak Depok is categorized as good; however, it still requires improvement, particularly in strengthening parental involvement. Effective collaboration between the school and parents is essential to ensure that positive character habits developed at school are consistently practiced in students’ daily lives at home.